THE ENVIRONMENTAL HEALTH OF THE GOIÁS JUDICIARY SERVERS: ADVANCES AND PERSPECTIVES BASED ON DATA FROM THE MUNICIPALITY OF LUZIÂNIA-GO (CIPEEX, 2023)
In this study, a considerable rate of absenteeism due to illness was evidenced amongthe employees of the Luziânia District - GO. The importance of health for the properfunctioning of the Goian Judiciary is highlighted, as the lack of adequate carenegatively affects the performance of their work activities. The research highlights therelevance of constitutional regulations, such as fundamental rights and the right tohealth, and also emphasizes the need for care regarding health-related changes,especially those related to modernization, and their impact on the employees. Theresults indicate the need to improve health care for public servants, with a focus onmental health, taking into account environmental, social, and technological factors.This research paves the way for broader investigations on how the management of theJudiciary can ensure the quality of life of its employees in accordance with thefundamental right to health.
Keywords: Health; Society; Environment; Judiciary